The shoot apex of Casuarina (Casuarinaceae) - Flores, E. M. (Revista de Biología Tropical, 1978)
The shoat apex of Casuarina has a uni-layered tunica. The corpus grades into a peripheral zone and a central zone which forms the pith. The embryonic shoat is conspicuously developed and exhibits several leaf primordia. Leaves are whorled, scale-like, linear lo lanccolate and mostly uni-veined. Except in their distal portions, the Ieaves of a whorl are concrescent along their lateral margins, forming a sheath which covers the base of the internade above the base of the whorl. The free apices are either valvate or laterally imbricate. There is a correlation between the number of leaf primordia produced and the size of the growth centers from which they develop. The area of the shoot apex in transection, as well as the perimeter of the circumference are not correlated with this phenomenon. The various concepts of the limits of the leaf in Casuarina are described